Integration of Islamic Law in Regional Development in Indonesia - Mohamad Hidayat Muhtar; Yogi Muhammad Rahman; Belardo Prasetya Mega Jaya; Awad Al Khalaf; Irma Suryani (Institut Agama Islam Negeri Batusangkar, 2023)
Indonesia has introduced Islamic-based development programs, but challenges such as different interpretations, incompatibility between Islamic law and the national legal system, political influence, and the integration of Islamic values in sustainable development continue to hinder the implementation of Islamic legal approaches in regional development. This study aims to analyze the integration of Islamic legal concepts in regional development from an economic, social, political and environmental perspective and to identify concrete policies or programs that can be implemented to apply a holistic and sustainable approach to Islamic law in regional development. This research is categorized as normative legal research using primary and secondary legal materials in statutory and library documents (books, journals, reports and internet sources) and analyzed using a philosophical and analytic approach. According to the findings, the problem can be solved by creating an Islamic-based development program that considers economic, social, political, and environmental factors and guarantees the program's sustainability. Increasing community participation and involvement in the planning and implementing Islamic-based development programs and strengthening oversight of the use of funds and the environmental impact of development activities are possible solutions. Based on the findings of this research, it is recommended that a microfinance initiative based on Islamic principles be established in the area. Integrating Islamic principles and considering Indonesia's social diversity are prerequisites for the success of an Islamic legal approach to regional development.